Drug-drug interactions of immunosuppressants and other drugs in kidney post-transplant recipients - Umana-Rivas , Mariel; Soares de Britto, Evelin; Santana da Silva Soares, Leticia; Rubens Ramos de Freitas, Geraldo; Alejandra Saavedra, Pamela; Queiroz Arimatea, Gustavo; Dias Gonçalves, Priscila; Galato, Dayani (Clinical and Biomedical Research, 2023)
Introduction: Immunosuppressants (ISS) are the most crucial tools used in the therapeutic regimens of transplant recipients. Nevertheless, these drugs are not the only ones adopted by patients; therefore, knowing the possible drug-drug interactions (DDIs) between immunosuppressants and other drugs commonly used in kidney transplant recipients is essential to ensure the effectiveness and safety of treatments. Objective: Analyze the DDIs between the immunosuppressants and other commonly used medications on kidney transplant adult recipients with active medical records undergoing post-transplant follow-up for 4.4 years (mean). Methods: First, we performed a cross-sectional study based on patients’ records, in which the patient’s profile and drugs used were examined, and after we analyzed DDIs by the Micromedex Drug Interactions ® database. Results: We analyzed 176 patients with a mean age of 47.6(± 12.5); most were male (67.7%), and the majority received a kidney from a deceased donor (81.4%). Patients were exposed to 15.0 (±5.4) different medicines after the transplantation, and 7.4 (±4.0) of these medicines were simultaneous. After analyzing the DDIs according to the severity of interaction, documentation quality interaction effect, clinical management and probable interaction mechanism, the most frequent interaction was with tacrolimus, classified as moderate, and the 3 major causes of interaction occurred with azathioprine according to the Micromedex database. The primary medicines involved with immunosuppressant interactions were proton pump inhibitors, ranitidine, domperidone, amlodipine, enalapril, allopurinol, cyclobenzaprine, amitriptyline, fluoxetine, and ciprofloxacin. These DDIs’ effects were related to, mainly, increase their immunosuppressant activity. Discussion: Although the immunosuppressants analyzed lacked many clinical DDIs significance with other medicines, the healthcare team needs to monitor their DDIs’ effects to prevent and minimize side effects in transplanted recipients.